Impact of Online Consumer Reviews on Hotel Booking Intentions: The Case of Pakistan - Danish, Rizwan Qaiser; Hafeez, Shahid; Ali, Hafiz Fawad; Shahid, Rabia; Nadeem, Kashif (European Scientific Journal, ESJ, 2019)
This study is aimed at empirically investigating the influence of online consumer reviews such as realism, positive reviews, negative reviews and volume of online reviews on hotel booking intentions in Pakistan through mediational mechanism. Data was collected from 250 part-time business graduates of University of Punjab, the largest Public-Sector University of Provincial Capital of Pakistan. SPSS and AMOS were carried out to analyze the results and determine the impact of online reviews on hotel booking intentions. Results indicated that realism, the volume of reviews and positive reviews are the most influential dimensions of online consumer reviews. Moreover, trust act as an intervening variable between positive reviews, the volume of reviews, realism and hotel booking intentions. Empirical analysis also indicated that negative online reviews have no direct and indirect impact on hotel booking intentions of online customers. This study is an effort in proposing a combination of online consumer reviews dimensions in determining Hotel Booking Intentions.